Pengaruh Kuliatas Pelayanan, Pengalaman, dan Ulasan Online Terhadap Kepuasan Pelanggan - Afrilianti, Lisa; Tuti, Meylani (Indonesian Journal Publisher, 2024)
The objective of this study is to examine the impact of service quality, experience, and online review of influence overall guest satisfaction at the hotel. Data was gathered during October-December 2023 at Swiss-Belresidences Kalibata. Purposive sampling was used to obtain a sample size of 151 visitors who agreed to fill out the survey. The data analysis technique employed was the Structure Equation Model, using the SmartPLS software. The reseacrh findings indicate that the three distinct reseacrh variables, namely of service quality, experience, online review, significantly impact satisfaction guest at the hotel. This demonstrates the hotel success for guest give the nice of experiences to online review. Service quality a consistanly give positive contributions made by employees to the guest get beyond expectation of experience at the hotel. Satisfaction guest will be give impact positive to hotel, cause if more then positive online review for others customer believe it nice and recommended and also many of guest will be loyality. Companies that consistently improve and maintain service quality, good customer experience for hotels, and good online reviews will get satisfaction from customers and build good long-term relationships between customers and the company.